α7-Nicotinic Acetylcholine Receptor activation modulates BV2 microglial plasticity via miR-21/TNF-α/NFκB in oxygen–glucose deprivation/reoxygenation - Hasan, Mohammad Yusuf; Md Roslan, Azim Haikal; Azmi, Norazrina; Mohamed Ibrahim, Norlinah; Arulsamy, Alina; Lee, Vanessa Lin Lin; Siran, Rosfaiizah; Vidyadaran, Sharmili (Springer, 2024)
Elevated inflammatory reactions are a significant component in cerebral ischemia–reperfusion injury (CIRI). Activation of α7-Nicotinic Acetylcholine Receptor (α7nAChR) reduces stroke-induced inflammation in rats, but the anti-inflammatory pathway in microglia under CIRI condition remains unclear. This study employed qRT-PCR, protein assays, NanoString analysis, and bioinformatics to examine the effects of PNU282987 treatment (α7nAChR agonist) on BV2 microglial functional differentiation in oxygen–glucose deprivation/reoxygenation (OGDR) condition. OGDR significantly increased the gene expression of pro-inflammatory markers such as TNF-α, IL-6, and IL1β, while α7nAChR agonists reduced these markers. The anti-inflammatory gene marker IL-10 was upregulated by α7nAChR agonist treatment. Downstream pathway marker analysis showed that both gene and protein expression of NFκB was associated with anti-inflammatory effects. Blocking microRNA-21 with antagomir reversed the anti-inflammatory effects. NanoString analysis revealed that microRNA-21 inhibition significantly affected inflammation-related genes, including AL1RAP, TLR9, FLT1, PTGIR, NFκB, TREM2, TNF, SMAD7, FOS, CCL5, IFIT1, CFB, CXCL10, IFI44, DDIT3, IRF7, OASL1, IL1A, IFIT2, C3, CD40, STAT2, IFIT3, IL1RN, OAS1A, CSF1, CCL4, CCL2, CCL3, BCL2L1, and ITGB2. Enrichment analysis of upregulated genes identified Gene Ontology Biological Processes related to cytokine responses and TNF-associated pathways. This study highlights α7nAChR activation as a key regulator of anti-inflammatory responses in BV2 microglia under OGDR conditions, with micro-RNA21 identified as a crucial mediator of receptor-driven neuroprotection via the TNF-α/NFκB signalling pathway.